UROPATHOGENS AND THEIR RESISTANCE PATTERN IN URINARY TRACT INFECTION CASES OF TERTIARY CARE HOSPITAL, BHOPAL - kaur, surender; Awari, Abhijit (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Urinary tract infections (UTIs) are an increasing public health problem caused by various uropathogens. To assess the adequacy of empirical therapy, an antibiogram of the bacteria responsible for UTI in patients coming to the tertiary hospital, Bhopal was evaluated for 13 months. Methods: In this prospective and observational study, all urine samples from patients of a tertiary care hospital collected at the Department of Microbiology, Peoples College of Medical Sciences and Research Centre, Bhopal, from January 2014 to January 2015 were processed. A sample with more than 105 CFU/mL of bacteria was considered positive, the bacteria were identified, and antibiotic susceptibility profile was characterized. Results: A total of 283 urine samples from suspected UTIs were analyzed, for which identification of bacteria and antimicrobial susceptibility testing were done. Overall, 56.53% were culture positive with a predominance of female patients (70.62%). Females 26–35 years old and males ≥46 years old showed maximum culture positivity. Escherichia coli (55.7%) was the most commonly isolated microorganism, followed by Klebsiella pneumoniae (24.8%). Isolated uropathogens were predominantly resistant to Ampicillin, Amoxycillin clavulanic acid, Cefotaxime, Ceftazidime, Cotrimoxazole, and Nalidixic acid. Conclusion: Our study confirms a global trend toward increased resistance to most antibiotics. We emphasize the formulation of antibiotic policy for a particular geographical area. E. coli was the most common uropathogen. Nitrofurantoin, Fluoroquinolones, Amikacin, and Piperacillin/tazobactam were the most effective antibiotics against uropathogens.